Morality, practice and economy in a commercial seal hunting community - Sellheim, Nikolas Peter (Arctic Anthropology, 2015)
In small social groups dependent on specific resources it is difficult to separate actions, moral understandings and the resource itself. It is the response to the affordances of a given environment that shapes the moral framework of social interaction. Therefore, also changes in the market sphere impact the conscious and unconscious actions relating to the affordances of the environment as well as a community’s socio-economic values. It is argued that moral relativism is justified when it is approached through an affordance-lens, meaning that if the role and relevance of a resource for a community is not understood its moral environment cannot be understood either. With ethnographic data stemming from the sealing season 2013 in a fishing and sealing community in northern Newfoundland this interplay of morality, practices and socio-economic values is documented.